2016
DOI: 10.1039/c5ra24735g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of cadmium using facile functionalized of mesoporous silica via a biomimetic coating

Abstract: A mesoporous material (DMOS), prepared by grafting polydopamine onto meso-structured silica (MOS), was developed as a sorbent to sequestrate Cd2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…The limit of detection (LOD) and the relative standard deviation (RSD, n = 6) of Cd were 0.1 µg/L and 1.0% with a preconcentration factor of 10, respectively. The LOD that was obtained in this study was the same as that reported by using resin for preconcentration [14], both are one magnitude smaller than the value obtained by using amino-functionalized mesoporous sorbent for Cd(II) preconcentration [22].…”
Section: Limit Of Detectionsupporting
confidence: 78%
See 3 more Smart Citations
“…The limit of detection (LOD) and the relative standard deviation (RSD, n = 6) of Cd were 0.1 µg/L and 1.0% with a preconcentration factor of 10, respectively. The LOD that was obtained in this study was the same as that reported by using resin for preconcentration [14], both are one magnitude smaller than the value obtained by using amino-functionalized mesoporous sorbent for Cd(II) preconcentration [22].…”
Section: Limit Of Detectionsupporting
confidence: 78%
“…The adsorption capacity (qmax) and adsorption constant (KL) were 28.5 mg/g and 0.14 L/mg, respectively. When comparing qmax reported in this study with the reported values for other adsorbents (4-137 mg/g) [22], qmax reported in this study is in the medium rank. However, other adsorbents, like meso silica (MCM-48, SBA-15 etc.…”
Section: Quantification Of Attached Dmsa and Pda In Dmsa/pda/znosupporting
confidence: 54%
See 2 more Smart Citations
“…Typical peaks at 467 cm −1 , 796 cm −1 and 1086 cm −1 corresponded to the bending vibration, symmetric stretching and asymmetric stretching of Si-O-Si bonds from all of the samples, suggesting that the structure of Meso-Onion-S was well preserved in DPMS and LCS@DPMS23. Characteristic band at 962 cm −1 represented the symmetric stretching vibration of Si-OH groups24. The adsorption peak at 1495 cm −1 of DPMS was belong to the stretching of benzene ring in the polydopamine17, which indicated the successful immobilization of dopamine.…”
Section: Resultsmentioning
confidence: 93%